Mechanical spectroscopy of MgB2 containing SiC - Silva, M. R. [UNESP]; Silva, L. B.S.; Rodrigues Junior, D.; Grandini, C. R. [UNESP] (De Gruyter, 2015)
The compound magnesium diboride (MgB2) has been well-known since the 1950s; however, its superconducting properties were unknown. Intrinsic characteristics of MgB2 make this material a promising candidate for technological applications, although the low value of the irreversibility field and the decrease in critical current density with the increase in the magnetic field considerably reduce its utility. The present work aimed to study the effect of carbon-based doping on anelastic properties of MgB2 as measured by mechanical spectroscopy. The samples were prepared by using the powder-intube method. The samples were made with 5, 7.5, and 10 wt.% of silicon carbide (SiC). The results reveal complex mechanical loss spectra caused by the interaction between point defects and surface defects in the crystalline lattice of MgB2.
Keywords: Anelasticity; Internal friction; Mechanical spectroscopy; MgB2; SiC